Perancangan Alat Pemberi Pakan Ikan Otomatis dengan RTC DS3231 Berbasis Microcontroller Arduino Uno - Yuda Febryanto; Teuku Radillah; Kiki Ameliza (The Indonesian Journal of Computer Science, 2022)
Fish feed is a mixture of various food ingredients (commonly called raw materials), both vegetable and animal, which are processed in such a way that they are easy to eat and digest as well as a source of nutrition for fish that can produce. energy for their lives. Fish farming is a hobby that many people enjoy from the past until now because of its easy care and maintenance. It's just difficult when a person travels for a long time to several days and thinks of feeding his pet fish. This research was designed with library methods and practical methods. The result of this research is that by making a tool that can make it easier for someone to feed, then the time it takes for the tool to provide 2.4 grams of feed is 1 second. with this automatic feeding tool it can make it easier for ornamental fish fans in feeding fish from manual system moved to automatic system.